The Effects of Understanding on Islamic Consumption, Price, and Motive on the Decision to Purchase Mobile Games’ Online Virtual Item - Fadhil, Muhammad Faisal; Anggraini, Ika Khusnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
With the rapid digitalization, Indonesia has seen an increase in internet users and the growth of sectors like online gaming. This phenomenon has led to new consumption patterns, such as purchasing virtual items through in-game top-ups, which can have negative effects. Based on several studies and the urgency from an Islamic economic perspective, this research aims to analyze the influence of Islamic consumption understanding, price, and rational and emotional motives on the decision to purchase mobile games’ online virtual item. The method used is descriptive quantitative with binary logistic regression analysis. The results show that Islamic consumption understanding has a significantly negative influence on purchase decisions, while emotional motives have a significantly positive influence. However, price and rational motives do not show a significant impact. This study highlights the importance of the younger generation, especially Generation Z, in considering Islamic consumption principles when making purchase decisions, rather than relying solely on emotions. Abstrak Dengan pesatnya digitalisasi, Indonesia mengalami peningkatan pengguna internet dan pertumbuhan sektor-sektor seperti game online. Fenomena ini memunculkan pola konsumsi baru, seperti pembelian item virtual melalui top-up dalam game, yang dapat berdampak negatif. Berdasarkan beberapa kajian dan urgensinya dalam perspektif ekonomi Islam, penelitian ini bertujuan untuk menganalisis pengaruh pemahaman konsumsi Islami, harga, serta motif rasional dan emosional terhadap keputusan pembelian barang virtual pada mobile game. Metode yang digunakan adalah deskriptif kuantitatif dengan analisis regresi logistik biner. Hasil penelitian menunjukkan bahwa pemahaman konsumsi Islam mempunyai pengaruh negatif signifikan terhadap keputusan pembelian, sedangkan motif emosional mempunyai pengaruh positif signifikan. Namun harga dan motif rasional tidak menunjukkan pengaruh yang signifikan. Studi ini menyoroti pentingnya generasi muda, khususnya Generasi Z, dalam mempertimbangkan prinsip konsumsi Islami ketika mengambil keputusan pembelian, dibandingkan hanya mengandalkan emosi.